Considering the Needs of the Church: A Response to Craig Blomberg - VERSEPUT, DONALD J. (2001)
It is necessary for the academy to listen carefully to the church, to appreciate more fully its new orientation and its changing needs. Three topics are especially pressing: (1) We must acquaint our students with the cultural experiences of early Christianity, in order to learn again how to make biblical theology relevant to our society. (2) The distinctives of biblical and Christian ethics need to be carefully probed. (3) The relevance of biblical theology for spirituality needs to be investigated afresh.